20 Forage Production and Nutritive Quality of Dual-purpose Wheat Managed Under Three Different Grazing Frequencies in the Southeastern United States. (8th March 2022) - West, Micayla H; Mullenix, M Kim; Rabinowitz, Adam N; Smith, W Brandon; Carrell, Russell C; Dillard, Leanne L
Abstract: Grazing of dual-purpose wheat is an established management system in the Great Plains regions of the United States. Varietal and climatic differences between regions has limited use of dual-purpose systems in the Southeast. The objective of this study was to evaluate four wheat varieties, [feed wheat (mixed variety, Feed), seed wheat ('GA Gore') and two forage varieties, 'AGS 2024' (AGS) and 'Pioneer 26R41' (Pioneer)], under three grazing treatments [no-grazing (NG), low frequency (LF), high frequency (HF)]. The experiment was a randomized complete block design (n = 4) using mob-grazing. Forage samples were taken using three 0.1m 2 -quadrats before (Pre) and after (Post) each grazing event. Crude protein (CP), neutral detergent fiber (NDF) and acid detergent fiber (ADF) were determined on all Pre samples. Wheat grain yield was determined at the end of the season. Data were analyzed using PROC GLIMMIX of SAS (SAS Inst., Cary, NC), a < 0.05. Pre-grazed, AGS seasonal forage production was greater (P < 0.01) than all other varieties (1, 517 kg/ha vs 1, 031 kg/ha, respectively). Post-grazing biomass from AGS and Pioneer was greater than GA Gore (817 vs 512 kg DM/ha, respectively; P = 0.04). Pre-grazing, Feed, GA Gore and Pioneer had greater (P < 0.01) CP than AGS (31.6 vs. 30.1%, respectively). The concentration of NDF was greatest for AGS (39.1%) compared with all other varieties (34.9%, P < 0.01). Grazing frequency did not affect CP (P = 0.67). The NG plots had greater NDF and ADF than LF and HF (37.5 vs. 35.2% and 19.8 vs. 18.6%, respectively; P < 0.01). Pioneer had the greatest grain yield but was not different from AGS (57.6 and 52.4 kg/ha, respectively; P = 0.41). Management of wheat as a dual-purpose crop is feasible in the Southeast. More information is needed to determine the economic impact of this management practice.